Studies in Ishchali Documents - Greengus, Samuel (1986)
215-236: Copies, collations and corrections to Lutz, UCP 10/1. 237-252: Copies of new Ishchali Tablets in the Collection of the Lowie Museum of Anthropology, University of California, Berkeley (UCLMA).